Perancangan Sistem Keamanan Website Dengan Metode Hill Chiper - Marpaung, Adetya Maharani; Husnah, Fauziatun; Efita, Sinta Dara; Nasution, Adnan Buyung (Jurnal Sains dan Teknologi (JSIT), 2022)
Security is a protection of something that is considered bad or unfavorable and can be detrimental. A website collection of site pages, which are usually summarized in a domain or subdomain, which is located within the World Wide Web (WWW) on the Internet. The WWW consists of an entire website that is publicly available. along with the development of the times the website is increasingly developing through the hands of programmers and developers so that the website is easily accessible, the Hill cipher is a polygraphy based on linear algebra. Each letter is represented by the modulo number 26. With a simple scheme A = 0, B = 1, ..., Z = 25 is used, each block of n letters (considered an n-component vector) multiplied by an inreversible matrix n × n, against a modulus of 26. The Progress of the Times, especially in the field of Technology, makes many people try to steal websites, in an unexpected way and can harm programmers or developers, therefore researchers make applications as a solution to maintain website security by using the Hill Cipher Cryptography method type symmetric encryption algorithm. and for its safety to be better, So the researcher added the 3x3 order as a verification of data encoding. So that programmers and developers can maintain and protect the website that has been created.